2014
DOI: 10.1134/s0013873814060037
|View full text |Cite
|
Sign up to set email alerts
|

The effect of toxin-producing Fusarium fungi on behavior of the rice weevil Sitophilus oryzae (Coleoptera, Dryophthoridae)

Abstract: The paper describes laboratory tests in which the behavior response of adult rice weevils Sitophilus oryzae L. to the presence of seven species of micromycetes of the genus Fusarium (F. graminearum, F. culmorum, F. cerealis, F. poae, F. sporotrichioides, F. langsethiae, and F. sibiricum; 3 strains for each species) infecting cereals was characterized. The chemicals of unkown structure, released by the fungi, can have both attractive and repellent effects on the weevils; in some cases a neutral response was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…The detected VOCs emitted by Fusarium fungi most probably include metabolites which act as attractants or repellents for insects coexisting with then and, probably, favor their dispersal and adaptation to the environment. In the experiments aimed at revealing semiochemical interactions between various Fusarium species and the rice weevil, associated with their development with cereals, the beetles showed different reactions on the studied strains . The low pathogenic strains F. langsethiae MFG93001 and F. poae MFG103403, grown both on PSA and on autoclaved wheat kernels acted as attractants on insects.…”
Section: Discussionmentioning
confidence: 99%
“…The detected VOCs emitted by Fusarium fungi most probably include metabolites which act as attractants or repellents for insects coexisting with then and, probably, favor their dispersal and adaptation to the environment. In the experiments aimed at revealing semiochemical interactions between various Fusarium species and the rice weevil, associated with their development with cereals, the beetles showed different reactions on the studied strains . The low pathogenic strains F. langsethiae MFG93001 and F. poae MFG103403, grown both on PSA and on autoclaved wheat kernels acted as attractants on insects.…”
Section: Discussionmentioning
confidence: 99%
“…The attractiveness of EPF for hosts or predators is much less common than repellency. Fungi Beauveria bronginiartii and M. anisopliae were attractive for collembolans [46], certain species of fungi of the genus Fusarium were attractive for rice weevil beetles [47]. The attractiveness of L. lecanii strain Vl 5 for O. laevigatus requires further study; it may be related to the peculiarities of the VOC composition of the mycelium of this strain.…”
Section: Resultsmentioning
confidence: 99%
“…Results provided by this study show that the B. bassiana strain inflicted a repellent effect on both insect species. Many studies revealed that insects tend to avoid the presence of fungal entomopathogens (16,17,23). This behavior has been attributed to volatile compounds released by fungi and to the capacity of insects to detect these specific signals.…”
Section: Discussionmentioning
confidence: 99%